A digital analysis comparing the surface staining characteristics of two commercially available porcelains on exposure to commonly consumed beverages - Nitasha Gandhi; Surbhi Mehdiratta; Nirmal Kurian; Neethu Roy; Vijay Alageshan; George Abraham (Wolters Kluwer Medknow Publications, 2019)
Aim: This in vitro study aimed to evaluate the color stability of two commercially available porcelain systems (Vita VMK®, VITA Zahnfabrik GmbH and Ceramco-3, Dentsply, India) against discoloration caused by commonly consumed beverages using digital analysis. Materials and Methods: Sixty porcelain samples in disc form were fabricated and divided into two groups (Ceramco-3® and Vita VMK®) consisting of thirty samples each. They were photographed digitally utilizing CIELAB system to obtain the baseline L*, a*, b* values. Samples were then immersed in test solutions for 180 days and the posttreatment images of the test materials were acquired at the 30th, 90th, and 180th day. All L*, a*, and b* values were analyzed by a graphic software, and the total color change (ΔE*) of each specimen was calculated. Statistical Analysis Used: Statistical analysis of the mean ΔE values among the groups was achieved by one-way analysis of variance paired Student t-test, post hoc Tukey's honest significant difference test, and the level of significance was set as 0.05. Results: Statistical analysis did not reveal a significant difference between the groups with the Group II (Vita VMK®) showing slightly more discoloration as compared to Ceramco-3® when immersed in all the test samples. It was also observed that both the feldspathic porcelains exhibited a greater color change when immersed in coffee when compared to tea. Conclusion: Both Ceramco-3® and Vita VMK® after immersion in test solutions showed minimum color change (i.e., maximum color stable) in water units and maximum color change in coffee with Vita VMK® exhibiting more change than Ceramco-3®.